1983
DOI: 10.1180/claymin.1983.018.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between chemical, physical and mineralogical characteristics of the Rupelian Boom Clay, Belgium

Abstract: The Boom Clay is an important raw material for the Belgian structural clay products industry. It can be divided into several lithological sub-units. In order to obtain an insight in the parameters which characterize these different units, and which affect the overall properties of the clay, a detailed chemical, physical and mineralogical analysis was carried out. Pearson correlation coefficients were calculated between the variables, which were then placed in four correlation groups: a quartz/clay mineral grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Remarkably, the organic matter shows a moderate, positive correlation with the clay content, while the pyrite does not. In a comparable study on Belgian Boom Clay for the clay products industry, the same factors and correlations were observed (Decleer et al, 1983), yet Decleer et al (1983) observed a clear correlation between organic matter, pyrite and the clay mineral content. According to the authors, this correlation is mainly sedimentological and reflects reducing conditions.…”
Section: Discussionsupporting
confidence: 60%
“…Remarkably, the organic matter shows a moderate, positive correlation with the clay content, while the pyrite does not. In a comparable study on Belgian Boom Clay for the clay products industry, the same factors and correlations were observed (Decleer et al, 1983), yet Decleer et al (1983) observed a clear correlation between organic matter, pyrite and the clay mineral content. According to the authors, this correlation is mainly sedimentological and reflects reducing conditions.…”
Section: Discussionsupporting
confidence: 60%
“…4). Table 1 (Decleer et al, 1983;AlMukhtar et al, 1996) presents the mineralogical composition of Boom clay. The clay fraction is dominant (50-62% , 2 ìm).…”
Section: Materials and Sample Preparationmentioning
confidence: 97%
“…Therefore, its bulk chemical composition and bulk physical and chemical properties are very well known. Classical studies include mineralogical, geochemical and granulometric investigations, comprising solid phase mineralogical characterisation via X-ray diffraction (Vandenberghe, 1974(Vandenberghe, , 1978Decleer et al, 1983;Laenen, 1997;Zeelmaekers, 2011), Fourier transform infrared spectroscopy (Wouters et al, 1999;FUNMIG, 2008), thermal gravimetric analysis (FUNMIG, 2008), surface area analysis (Baeyens et al, 1985;Honty et al, 2010) and cation exchange capacity measurements (Baeyens et al, 1985;Griffault et al, 1996;Honty et al, 2010). For elemental analysis, atomic absorption and emission spectroscopy (AAS/AES), X-ray fluorescence, inductively coupled plasma mass spectrometry (ICP-MS) and instrumental neutron activation analysis (INAA) were applied (e.g.…”
mentioning
confidence: 99%
“…For elemental analysis, atomic absorption and emission spectroscopy (AAS/AES), X-ray fluorescence, inductively coupled plasma mass spectrometry (ICP-MS) and instrumental neutron activation analysis (INAA) were applied (e.g. Decleer et al, 1983, Decleer & Viaene, 1993Laenen, 1997;De Craen et al 2000;Zeelmaekers, 2011).…”
mentioning
confidence: 99%